Man-Machine Interactions 4 4th International Conference on Man-Machine Interactions, ICMMI 2015 Kocierz Pass, Poland, October 6-9, 2015 - Gruca, Aleksandra; Brachman, Agnieszka; Kozielski, Stanisław; Czachórski, Tadeusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides an overview of the current state of research on development and application of methods, algorithms, tools and systems associated with the studies on man-machine interaction. Modern machines and computer systems are designed not only to process information, but also to work in dynamic environment, supporting or even replacing human activities in areas such as business, industry, medicine or military. The interdisciplinary field of research on man-machine interactions focuses on broad range of aspects related to the ways in which human make or use computational artifacts, systems and infrastructure.   This monograph is the fourth edition in the series and presents new concepts concerning analysis, design and evaluation of man-machine systems. The selection of high-quality, original papers covers a wide scope of research topics focused on the main problems and challenges encountered within rapidly evolving new forms of human-machine relationships. The presented material is structured into following sections: human-computer interfaces, robot, control, embedded and navigation systems, bio-data analysis and mining, biomedical signal processing, image and motion data processing, decision support and expert systems, pattern recognition, fuzzy systems, algorithms and optimisation, computer networks and mobile technologies, and data management systems.
Invited Papers -- Human-Computer Interfaces -- Robot Control, Embedded and Navigation Systems -- Bio-Data Analysis and Mining -- Biomedical Signal Processing -- Image and Motion Data Processing -- Decision Support and Expert Systems -- Pattern Recognition -- Fuzzy Systems -- Algorithms and Optimisation -- Computer Networks and Mobile Technologies -- Data Management Systems.
Keywords: Computational intelligence; Artificial intelligence; User interfaces (Computer systems).; Human-computer interaction; Computational Intelligence; Artificial Intelligence; User Interfaces and Human Computer Interaction